Pengaruh pembiayaan syariah terhadap profitabilitas bank dengan BOPO sebagai pemoderasi - Trisila, Juwanto; Nabila, Rifda (Journal of Accounting and Digital Finance, 2023)
This research aims to determine the effect of mudharabah financing, musyarakah financing, and murabahah financing on profitability with BOPO as a moderating variable in Sharia commercial banks in 2016-2020. This type of research is quantitative research using secondary data in the form of panel data. The population in this study was 14 Sharia Commercial Banks, and 12 banks were selected as samples using the purposive sampling method. The data analysis method uses a moderated regression analysis approach. This research shows that mudharabah financing has a positive and significant effect on ROA, musyarakah financing, and murabahah financing has no effect on ROA. BOPO is able to moderate mudharabah financing against ROA, BOPO cannot moderate musyarakah financing and murabahah financing.